Abundance measurements of H2O and carbon-bearing species in the atmosphere of WASP-127b confirm its supersolar metallicity. Issue 3 (13th October 2020) - Spake, Jessica J; Sing, David K; Wakeford, Hannah R; Nikolov, Nikolay; Mikal-Evans, Thomas; Deming, Drake; Barstow, Joanna K; Anderson, David R; Carter, Aarynn L; Gillon, Michael; Goyal, Jayesh M; Hebrard, Guillaume; et al.
ABSTRACT: The chemical abundances of exoplanet atmospheres may provide valuable information about the bulk compositions, formation pathways, and evolutionary histories of planets. Exoplanets with large, relatively cloud-free atmospheres, and which orbit bright stars provide the best opportunities for accurate abundance measurements. For this reason, we measured the transmission spectrum of the bright ( V ∼ 10.2), large (1.37  R J ), sub-Saturn mass (0.19  M J ) exoplanet WASP-127b across the near-UV to near-infrared wavelength range (0.3–5  μ m), using the Hubble and Spitzer Space Telescopes . Our results show a feature-rich transmission spectrum, with absorption from Na, H2 O, and CO2, and wavelength-dependent scattering from small-particle condensates. We ran two types of atmospheric retrieval models: one enforcing chemical equilibrium, and the other which fit the abundances freely. Our retrieved abundances at chemical equilibrium for Na, O, and C are all supersolar, with abundances relative to solar values of 9$^{+15}_{-6}$, 16$^{+7}_{-5}$, and 26$^{+12}_{-9}$, respectively. Despite giving conflicting C/O ratios, both retrievals gave supersolar CO2 volume mixing ratios, which adds to the likelihood that WASP-127b's bulk metallicity is supersolar, since CO2 abundance is highly sensitive to atmospheric metallicity. We detect water at a significance of 13.7σ. Our detection of Na is in agreement with previous ground-based detections, though we find a much lower abundance, and we also do not find evidence for Li or K despite increased sensitivity. In the future, spectroscopy with James Webb Space Telescope will be able to constrain WASP-127b's C/O ratio, and may reveal the formation history of this metal-enriched, highly observable exoplanet.